PENDIDIKAN MADRASAH DI INDONESIA - Alawiyah, Faridah (Jurnal Aspirasi, 2014)
Madrasah (Islamic school) has a strategic role in the development of the nation. Currently, madrasah is still considered as delivering second class education in Indonesia. This happens because madrasah has several major problems such as management problems and poor quality of education. This paper is intended to provide an overview on Islamic school’s education system, its problems, opportunities, and challenges. Madrasah has become a part of the national education system. Literature study was used as the method in this study by collecting secondary data from various sources and went through descriptive data analysis in detail. Various problems faced by madrasah were education management, gap between public and private madrasah, quality of madrasah, as well as curriculum to name but a few. On the other hand, madrasah also had its own strength with society’s better understanding to Islamic education that would turn that strength into opportunity and challenge for advancement of madrasah.